THE TENDENCY OF AGGRESSIVENESS IN ADOLESCENTS - Rizki Muliani; Nur Oktavia Hidayati; Afif Amrullah (Universitas Padjadjaran, 2021)
Aggressiveness is one of the common problems that often occur in adolescents. The tendency of emotional fluctuations in adolescents is one factor that makes adolescents vulnerable to aggressiveness. One form of aggressiveness that is currently rife among adolescents is student brawl. Aggressive actions such as student brawl result in a negative impact on victims and adolescents who become perpetrators of the brawl. This study aimed to discover the tendency of aggressivity in adolescents at YPGU Sumedang Vocational School. The method used in this study is the descriptive quantitative method. The variables studied were adolescents' tendency to cover dimensions as physical aggression, verbal aggression, anger, and hostility. The number of samples in this study was 162 respondents using an accidental sampling technique. The instrument used was adopted from the aggression questionnaire developed by Buss and Perry, which consists of 29 closed statement items. Data analysis used interval value ranges based on the length of the interval per class of the minimum and maximum values. This study's results are seen from the percentage in the category of low, moderate, and high. The results showed as many as 149 respondents (92%) have a moderate tendency of aggressivity. Based on the study results, it can be concluded that almost all adolescents in this study have a moderate tendency of aggressivity. Similarly, on the dimensions of aggressiveness measured, the average tends towards the moderate category. As for the dimensions of this aggressiveness, physical aggression has the greatest tendency than any other dimension, so it is advisable to further improve prevention programs' aggressiveness at YPGU Sumedang Vocational School.